The role of CSR and prestige in linking green recruitment to job pursuit intentions - Wulandaru, Diah Retno; Putri, Zaqiah Vivi; Ramadhani, Syafika Dhea Taqiya (Asian Management and Business Review, 2026)
Generation Z is recognized for its high level of environmental awareness, which shapes how they evaluate potential employers and respond to organizations that demonstrate sustainability commitments. This study examines the role of green recruitment (GR) in influencing job pursuit intention (JPI) among Generation Z in Indonesia by drawing on social identity theory and signaling theory. Specifically, the study investigates whether corporate social responsibility (CSR) and organizational prestige (OP) mediate the effect of GR on JPI. Using a sample of 106 Generation Z respondents, the data were analyzed using SmartPLS 3.0 to test seven proposed hypotheses. The results show that GR significantly enhances perceptions of CSR and OP, but it does not directly influence JPI. OP was found to have a positive effect on JPI, although it does not mediate the relationship between GR and JPI. Conversely, CSR serves as a significant mediator between GR and JPI, indicating that Generation Z job seekers respond more strongly to organizations that demonstrate genuine CSR engagement. However, CSR itself does not exhibit a direct significant effect on JPI, suggesting that applicants may prioritize organizations’ more concrete and visible attributes. Overall, the findings emphasize the important mediating role of CSR compared to OP and underscore the need for organizations to implement strategic GR practices that strengthen sustainability perceptions and enhance employer attractiveness. These insights provide practical guidance for organizations seeking to design recruitment strategies that are both effective and environmentally responsible.